Кількісний аналіз новел В. Стефаника та їх перекладів англійською мовою - Кульчицький, Ігор Маркіянович; Калимон, Юлія Олександрівна; Kulchytskyj, I. M.; Kalymon, Yu. O. (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статті розглянуто актуальність та перспективи використання методів і засобів квантитативної лінгвістики для дослідження української мови на прикладі новел В. Стефаника. Оскільки найефективнішими новітніми методами вивчення особливостей авторського стилю вважають квантитативні статистичні методи, вони стають дедалі актуальнішими з розвитком комп’ютерних технологій та програмного забезпечення. У нашому дослідженні ці методи застосовано для вивчення ідіостилю В. Стефаника на прикладі частини його новел і їх перекладів англійською мовою. Зокрема, здійснено квантитативний та порівняльний їх аналіз. Окрім цього, проведено порівняльний аналіз цих українських новел з 11- і 20-томним словниками української мови. Визна¬чено перспективні напрями подальших досліджень на основі отриманих результатів, що дасть змогу значно розширити спектр вивчення української мови загалом за допомогою статистичних методів. The article deals with topicality and prospects of quantitative linguistics methods and tools in studying the Ukrainian language on the example of short stories by V. Stefanyk. Nowadays anthropocentric aspects of linguistic phenomena study within cognitive linguistics have acquired great relevance, as can be observed by the growing number of studies devoted to the study of the individual idiolect. In particular, the study of writer’s idiostyle has become one of the leading areas of modern linguistics. According to modern linguists the most effective methods for such researches are quantitative statistical methods regarding to the development of computer technology and software. Statistical linguistics as a science that deals with the detection and quantitative description of the characteristics and patterns of language and speech is based on the fact that some quantitative characteristics and functional relationships between them may describe the language as a whole or its functional styles. Quantitative and comparative analysis of Stefanyk’s short stories and their corresponding English translations was carried out, as well as comparative analysis of data based on Ukrainian language short stories and 11- and 20-volume dictionaries of the Ukrainian language. Abovementioned procedures allowed to make corresponding conclusions about V. Stefanyk’s idiolect. Perspective directions of further research based on the obtained results were outlined concerning Ukrainian language as a whole by applying statistical methods.
Quantitative Analysis of V. Stefanyk’s Short Stories and their English Translations
Keywords: квантитативна лінгвістика s; quantitative linguistic; конкордансер; concordancer; статистичні методи; statistical methods